The Influence Of Training And Ability And Experience Work on The Performance of Contracting Personnel In M. Natsir Solok Hospital - Rika Maidina; Rasidah Nasrah; Ida Nirvana (Cita konsultindo, 2022)
The phenomenon that occurs in contract workers at M. Natsir Solok Hospital at this time shows that there are several senior employees who have long work experience or have worked for more than 3 years but have not improved their performance. Apart from that, with longer work experience, there are still few employees with sufficient work experience, less training. Most of the senior employees have the notion that training is only needed for new employees and is not part of the company's work plan in improving performance. The aim of this research is UTo determine the effect of training, work ability and work experience simultaneously on the performance of contract workers at the M. Natsir Solok hospital.This type of researchthis research is a quantitative research with sThe data source used in this study was in the form of questionnaires which were distributed and filled in by contract worker respondents at M. Natsir Solok Hospital. The population of this study were 52 contract workers at M. Natsir Solok Hospital.The test results show that training has an effect on the performance of contract workers as evidenced by using t count3.220 > t table 2.00958, and a significant value of 0.001 <0.05. Work ability affects the performance of contract workers with t count3.002 > t table 2.00958, and a significant value of 0.001 <0.05. Work experience affects the performance of contract workers with t count4.811 > t table 2.00958, and a significant value of 0.000 <0.05. The results show thattraining, ability, and work experience simultaneously affect the performance of contract workers obtained as evidenced by the Fcount value of 37.735 > Ftable of 2.79with a significance level of 0.000 because the probability is much smaller than 0.05.